(untitled) (Annals of Medical Research, 2021)
Aim: Pilonidal disease presents with acute abscess, sinuses, pits and scarring in the sacrococcygeal region. Surgical intervention is one of the treatment options of pilonidal disease. However, it has been a matter of debate, whether histological analysis of surgically resected pilonidal disease specimens would be necessary. Material and Methods: Medical records of the patients with pilonidal disease who underwent either primary excision and closure or modified Limberg flap surgery were reviewed retrospectively. The results of the histopathological examination of the pilonidal disease specimens were evaluated.Results: This study included 905 patients (686 male and 219 female) with pilonidal disease who were treated with surgical intervention. The mean age of the patients was 23.96±7.5 years. All surgically excised pilonidal disease specimens of the patients were histopathologically evaluated in order to rule out malignancy. No malignancy was detected.Conclusion: We conducted a Pubmed search with the term “pilonidal” between January 2000 and March 2019. We identified 91 patients with malignant degeneration arising on pilonidal disease in the English medical literature. The most common pilonidal disease associated malignancy was squamous cell carcinoma. Even it is rare, malignancy may accompany pilonidal disease. Therefore, even we have not encountered any malignancy in 905 patients with pilonidal disease, we still insist on histopathological examination of all surgically resected pilonidal disease specimens in order to rule out malignancy.